Surface finishing and residual stress improvement of chemical vapour deposited tungsten carbide hard coatings by vibratory polishing - Micallef, Christian; Walton, Karl; Zhuk, Yuri; Aria, Adrianus Indrat (Elsevier, 2022)
Hard coatings are widely used in several industries to improve the service life of engineering components. W/WC coatings deposited through chemical vapour deposition (CVD) have the capability of providing the required protection on parts with complex geometries, commonly used in high wear and corrosive environments. Despite the improvement in service life, a key important factor is the adherence to low roughness and tolerance specifications, necessitating the need of a post-coating finishing process. In this work the impact of vibratory polishing on W/WC coating was studied using a vibratory barrel setup and two types of ceramic-based media. An improvement in average Ra of 0.2–0.3 μm was achieved over a duration of 4 h with abrasive wear being the predominant polishing mechanism. Insignificant weight loss (<0.017 g) and hardness changes (−2 < ΔHV < 8) were confirmed while the compressive residual stresses of the coating were found to increase with process time (max Δσ = −1058.3 MPa)
Keywords: Vibratory polishing; Tungsten carbide; Surface roughness; Residual stress